Following Oxygen Consumption in Singlet Oxygen Reactions via Changes in Sensitizer Phosphorescence1. (28th November 2014) - Feng, Tingting; Grusenmeyer, Tod A.; Lupin, Max; Schmehl, Russell H.
Abstract This work reports an examination of singlet oxygen reactions with amino acid substrates by a method involving measurement of the change in phosphorescence intensity of the singlet oxygen sensitizer. The sensitizer, a Ru(II) bipyridyl complex covalently linked to pyrene, has long‐lived phosphorescence in N2 purged aqueous solutions (τ0 ~ 20 μs) that is nearly completely quenched by oxygen in aerated solutions. Irradiation of the complex in water containing sub mM concentrations of histidine, tryptophan and methionine results in a dramatic, easily visible increase in the phosphorescence intensity over a period of 10–100 s. Rate constants for singlet oxygen oxidation of each of the substrates can be obtained by using changes in the phosphorescence intensity in initial rate kinetic analysis. Rate constants obtained in this way compare favorably with those reported in the literature. The method represents a very simple approach for obtaining rate constants for singlet oxygen reactions with various substrates and the kinetics can be extended to nonaqueous solvents.